PENGENDALIAN PENCEMARAN LINGKUNGAN LIMBAH KILANG SAGU DI DESA SUNGAI TOHOR KABUPATEN KEPULAUAN MERANTI - Khairil Saleh; Zulkarnaini " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The purpose of this study was to determine pollution control, factors that inhibit pollution control in Sungai Tohor Village, Kepulauan Meranti Regency. The theoretical concept used is the control theory from Amirullah Harris Budiyono with performance measurement indicators, comparing achievements with standards, taking corrective actions. This study uses a qualitative method that is descriptive in nature, informational selection using snowball sampling. Techniques for collecting data through interviews, observation, and documentation. The results of this study indicate that the control carried out by the Department of Environment of the Meranti Islands Regency has not been effective, this shows that there has not been a change in river water quality towards a better one, and there is still a lot of pollution due to the disposal of sago waste along the Tohor River. Some influencing factors include, human resources, funds or costs, community participation. Keywords: Pollution, Control, Environment